Penyelesaian Sengketa Batas Wilayah Petuanan Masyarakat Hukum Adat Liliali Dan Kayeli - Bessy, Sitna Hajija; Lakburlawal, Mahrita Aprilya; Nirahua, Garciano (PATTIMURA Law Study Review, 2025)
Ulayat rights in the customary law community are the highest land control rights which contain two elements/aspects, namely private and public. Minister of Home Affairs Regulation Number 45 of 2016 concerning Guidelines and Confirmation of Village Boundaries, explains that the determination and confirmation of village boundaries is to create orderly government administration, providing clarity and legal certainty regarding the territorial boundaries of a village that meets technical and juridical aspects. Petuanan Liliali is in Liliali District and directly borders Petuanan Kayeli. However, in 2017, problems arose regarding the territorial boundaries between Petuanan Liliali and Petuanan Kayeli. The aim of this research is to determine and explain the territorial boundaries of customary law communities and the government's responsibilities in resolving the Petuanan Liliali area in relation to customary territory disputes. The research method used is an empirical juridical research method. The results of the research show that the resolution of the petuanan territorial boundary dispute was carried out in a traditional manner, namely a customary process with the initial stage of calling both parties to come to attend the customary process at the residence of Raja Liliali which was planned to find a solution and a way out so that this petuanan territorial boundary dispute case did not continue and prolonged and does not cause undesirable things that can harm both parties. The final stage will be carried out. After everything has been discussed, this final stage will be carried out to create peace points that have been agreed upon by Petuanan Liliali and Kayeli. The peace deed will be signed by all parties concerned in the mediation process related to the dispute over the boundaries of the Petuanan Liliali and Kayeli territories that occurred.